(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In this article, there were researched and discussed forms and signs of interreligious relations. Complicated cases of interreligious sfrives and conflicts were analysed and provided exact definitions of existing situations. The rewerecon ductedinvestigationsbasedondynamycandprogress (evolution) ofvariousreligiousstreamsduringlastseveralyears, their history, culture and traditions in the relevant regions, by method of comparative analysis with global research experiences.In order to stabilize and improve inter-religious relations, there were discussed various methods of influencing to the audience and presented, by drawing attention to incidents in various areas of society. Intergovernmental, interfaith, global and ecumenistic experiences were analyzed, based on which the ways of solving the most important tasks were considered, which today are of significant importance on the world stage.There were presented explanatory lectures (materials) to emphasise the importance of the local phenomenon of interreligious tolerance, based on the analysis of the principles of traditional religions and by comparing the attitudes of different non-traditional religious streams to representatives of other religions.Solutions have been proposed based on scientific research, to improve interfaith differences and to strengthen the stability of interfaith relations.The possible consequences of meeting or colliding of different groups with differentcultures, with different attitudes and ideology as a result of the possible influence and interaction of them were investigated.The postulates of inter-religious relations, in Buddhism, Judaism, Christianity, Islam connected to these issues were analyzed. For example, were proposed methods to caution and prevent the occurrence of preconditions leading to inter-religious discrimination, the spread of impatience towards to members of other religions, a decrease in tolerance, disunity and aggression. Key words: inter-religious relations, inter-religious conflicts, religion and culture, forms of interconfessional relations, inter-religious level.